Research Progress on Industrial Robots: A Review - Shinde, Vilas B.; Pawar, Padmakar J.; Gadakh, Vijay S. (Recent Patents on Mechanical Engineering, 2026)
The success of the fourth and upcoming fifth industrial resolution lies majorly in automation and robotics. Industrial robots perform various manufacturing-related tasks due to their autonomy, flexibility, and autonomous work in a complex environment. Applications including drilling, material transfer, loading and unloading machines, processing, assembling, and inspection, welding, spray painting, machining, and so on are common. The present work comprehensively summarizes all the pertinent work related to the industrial robot based on extensive literature review and patents, such as inverse kinematics problems, robot design, programming, scheduling, motion planning, and trajectory planning. In addition, the present work discusses various optimization algorithms employed in industrial robots. Furthermore, several recommendations for future research have been addressed.
Keywords: forward kinematics